A clinical study to evaluate the efficacy of Patoladi Kwath (SU. CH.) with or without Rasnadi Pradeh (CH. SU.) in cases of Vatarakta (W.S.R. to Gouty Arthritis) - GUPTA, DEEPIKA; Sachdev, Kamal; Garg, Richa (Journal of Drug Delivery and Therapeutics, 2019)
In Ayurveda, health means the state of Doshasamya, Agnisamya, Dhatusamya and Samanya Malkriya as well as wellness of Atmendriya and Mana1, which according to Acharya Charak is necessary to achieve Dharma, Artha, Kama & Moksha2, the ultimate aim of life. But it has become quite difficult due to the various health obstacles experienced by men during his routine life. The disease Vatarakta is one of them and the number of Vatarakta patient are increasing day by day. The status of Vatarakta is often compared with Gouty Arthritis in the allied sciences. As far as the treatment of Vatarakta/Gouty Arthritis is concerned various research works conducted from time to time, which had shown encouraging result, but still there are many Ayurvedic medicine whose effect has to be established in the management of Vatarakta/Gouty Arthritis based on latest scientific parameters. Acharya Charak has advocated the use of different Ghrit Yog, Tail Yog, Lepa, Pradeha, etc for external application in different types of Vatarakta for relieving pain, swelling, stiffness, burning, itching, etc. So, for this research work we selected Patoladi Kwath from Susrut Chikitsa Sthana 5 and Rasnadi Pradeh from Charak Sutra Sthana 3 to evaluate their efficacy in the management of Vatarakta (w.s.r. to Gouty Arthritis). For this research work 56 diagnosed patient of Vatarakta having age of 21 to 60 years were registered and sequentially randomized into two parallel groups. Leaving 6 dropout (3 from each group), 25 patients of group A were treated with 40 ml Patoladi kwath 2 times a day after meal for 90 days and 25 patients of group B were treated with 40 ml Patoladi kwath 2 times a day after meal with Rasnadi Praddeh for local application over affected joint in the evening for 90 days. The result of the treatment was accessed based on the improvement in terms of symptomatic relief and improvement in terms of Lab investigation i.e, decrease in Serum Uric Acid level and ESR.